The Birth and Life of Buildings: High-Resolution Analysis of Historical Building Trends through the Digitised Municipal Archive of Tel Aviv-Yafo - Elad Horn; Or Aleksandrowicz; Daniel Rosenberg; Ido Baum (European Journal of Geography)
Inconsistent temporal definitions of key events in a building's lifecycles, and especially of its "birth" date, usually impede a large-scale, high-resolution analysis of building trends and construction fluxes based on municipal building datasets. This study addresses this shortcoming by proposing a reproducible ontological dating formulation of major construction activities during a building's lifecycle using the building permit as the most common, reliable, and consistent indicator of a building's age. We tested this approach by analysing the Tel Aviv-Yafo Municipality's Engineering Administration Archive, which consists of around 5.3 million digitised documents spanning between 1920-2020 and arranged in more than 28,000 building files. We combined permit data with supporting taxation and construction completion documents to automatically extract the date of "birth" or major reconstruction of each of the dataset buildings. The resulting dataset enabled us to generate detailed diachronic maps of urban growth at the resolution of an individual building. Despite challenges such as data discrepancies and archival gaps, this analytical method highlights the value of working directly with raw administrative metadata to uncover valuable insights into historical transformations in the built environment. It also demonstrates the utility of building permits as critical indicators of economic and architectural activities. By applying this approach to urban-scale building datasets, it is possible to predict building ages with reasonable accuracy and, thus, to enhance the understanding of urban growth and transformation dynamics.